Propuesta para la evaluacion de desempeño, manual de funciones y valuacion de puestos por puntos en la empresa “PROALDE” en la ciudad de Santo Domingo de los Tsachilas - Briceño Castillo, Leidy (2014)
Santo Domingo ECUADOR today is in a time of growth in demand for products and services requiring companies organized growth. This research was developed in the company PROALDE producer and distributor of coffee bean and chifles, in order to improve organizational performance was proposed as general objective to develop a Manual Functions and Valuation number of points for Human Talent the company "PROALDE" city of Santo Domingo. For this the Revised Literary where concepts and related theory is onboard is relizó. An investigation of the history of the company was held, also analyzing their current situation. Goals to meet and conduct such research was proposed. For the realization of these objectives and in order to deepen the state of the company for that the materials and methods surveys was their most valued customers its staff, in order to obtain first hand and real. Note that for the proper execution of this study different methods and research techniques were applied, which helped us obtain relevant information that served us well in the development of the study "According to the results has been proposed to perform a Proposal Assessment of performance, user roles and job evaluation points in the company "PROALDE" in the city of Santo Domingo de los Tsachilas " As results that proposal will allow an evaluation of performance, function manual in order to keep the company growing in the market in an organized manner. This model is recommended to be enforceable and that we accept its directors, indicating that the proposal to run is feasible and viable for the organization therefore the proposal is accepted by the owners do in order to have a company with a better structure. Therefore the conclusions that PROALDE Company, unknown exactly all the functions of their jobs is presented, this problem is deepened by the absence of Functions Manual, Job Classification and Rating Points, then the Recommendations pose the same as a proper application of the proposal, and literature as a source of obtaining the information.